Pemanfaatan Kecerdasan Buatan dalam Pembuatan Powerpoint Otomatis untuk Para Guru dengan SlideAI.io - Aunurrahman Aunurrahman; Haratua Tiur Maria; Urai Salam; Venny Karolina; Warneri Warneri; Yayuk Dwi Astuti; Nurdiana Nurdiana; Suhardi Suhardi; Suapri Effendy (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
This community service research aims to introduce and train teachers in utilizing artificial intelligence to create automated PowerPoint presentations using the SlideAI.io platform. The activity method involves introducing the platform to teachers, training them in its use, and evaluating the presentations created. The activity was conducted in schools in the city of Pontianak. The results showed a significant increase in the efficiency of presentation creation, enhanced appeal and effectiveness of presentations, and the potential for improving student interest and understanding of the learning material. This research contributes to the development of educational technology skills among educators, strengthens innovative teaching methods, and enhances the quality of education at the school level.